2012
DOI: 10.1159/000337143
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Formation of Cerebral Microbleeds after Carotid Artery Stenting

Abstract: Background: Recent studies reported that cerebral microbleeds (CMBs), i.e. small areas of signal loss on T2*-weighted gradient-echo (GE) imaging, could develop rapidly after acute ischemic stroke. We hypothesized that CMBs rapidly emerge after carotid artery stenting (CAS). Objective: We investigated the frequency of and predisposing factors for CMBs after CAS. Methods: We retrospectively examined MRI before and after CAS in 88 consecutive patients (average age: 71.7 ± 7.2 years, average rates of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 41 publications
3
17
0
Order By: Relevance
“…16,17 This condition has gained particular consideration in the last years because studies have demonstrated that it is associated with the presence and outcome of cerebral strokes and with neurodegenerative disorders. [18][19][20] Some recent papers have indicated an association between the atherosclerotic disease of the carotid artery and the presence of CMBs, 7,21,22 and Saba et al 7 found that the presence and the degree of severity of CMBs are associated with the presence of some specific plaque subcomponents, namely the fatty components. The purpose of our study was to explore the potential association between the carotid artery plaque volume (and the volume of its subcomponents) and the CMBs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 This condition has gained particular consideration in the last years because studies have demonstrated that it is associated with the presence and outcome of cerebral strokes and with neurodegenerative disorders. [18][19][20] Some recent papers have indicated an association between the atherosclerotic disease of the carotid artery and the presence of CMBs, 7,21,22 and Saba et al 7 found that the presence and the degree of severity of CMBs are associated with the presence of some specific plaque subcomponents, namely the fatty components. The purpose of our study was to explore the potential association between the carotid artery plaque volume (and the volume of its subcomponents) and the CMBs.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of CMBs we found was 23.5% (16 of 68), and it is similar to other previously published papers. 16,[21][22][23][24] However, some recent papers have reported a very high prevalence of CMBs. 25,26 This difference can be explained by the fact that the detection of CMBs is reliant on the paramagnetic property of hemosiderin which disrupts the local magnetic field (the so-called "susceptibility effect") on T2*-weighted GRE.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the abnormal signal spot represented some metal because the MRI findings of the lesion included no MRI signals resulting in a signal void, a susceptibility artifact resulting in the high-intense halo and the "blooming" appearance, and no signal changes over time, and these characteristics completely consisted with those of cases that we previously reported as suspected metallic embolisms after endovascular coil embolization for cerebral aneurysms. 3) Besides embolism, hemosiderin deposition might be considered because microbleeds were reported to occur after CAS in approximately 10% of the cases 6,7) and the abnormal spot was low intensity in all the images. However, this was unlikely because the surrounding halo on T2 and DWIs and the "blooming" effect on SWI were inconsistent with hemosiderin.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 15 New CMBs could also occur shortly in 8% of patients after carotid artery stenting. 18 The development of CMBs was attributable to blood–brain barrier (BBB) disruption and small arteries or arteriole rupture. 4 , 5 Sudden reperfusion and hemodynamic changes after mechanical thrombectomy could aggravate the BBB disruption.…”
Section: Discussionmentioning
confidence: 99%
“… 14 16 New CMBs have also been reported to occur shortly after carotid artery stenting or cardiac valve surgery. 17 , 18 …”
Section: Introductionmentioning
confidence: 99%